The University Students’ Awareness of Hyperreality on Social Media and Problematic Social Media Usage: A Qualitative Study - Huri Deniz Karcı (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
How social media has changed people’s perception of reality is a question of debate in recent years. Excessive social media usage particularly among young people has begun to worry parents, educators and youth researchers. Hence; the study aims to detect how young people are aware of their social media usage and their ability to differentiate the reality between social media and their normal life. The 3rd grade Graphic Design students, consisting 30 persons of population, in a university in Konya started a social responsibility project called “ThisIsNotYourLife” in the first term of 2021-2022 academic year. Regarding the fact that those students have an awareness in a certain extent, the sample was crewed from this population. 27 of the population participated in the study to make an in-depth interview. Thematic analysis was employed depending on Baudrillard’s Simulations Theory and Griffiths’ addiction variables used in the BSMAS as SM addiction components. The study concluded young people could hold a balance between the reality of their normal life and social media life and control their social media usage if they are given an awareness task or training. The study is thought to make contributions to social media usage research and professionals who work on young people’s addiction behavior.